2014
DOI: 10.1017/s0950268814001897
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seafood regulations forVibrio parahaemolyticusinfection and verification by analyses of seafood contamination and infection

Abstract: Consumption of seafood contaminated with Vibrio parahaemolyticus causes foodborne infections, which are on the rise owing to increased consumption of raw seafood in Asia, Europe, North America, and other regions. V. parahaemolyticus infections have been common in Japan since the 1960s. Following an epidemic in 1997, the Japanese Ministry of Health, Labour, and Welfare instituted regulations for seafood in 1999, which appear to be reducing V. parahaemolyticus infections. In this review, we describe the scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Another national analysis has indicated that meat and meat products are the most common vehicle of VP infection (responsible for 18% of outbreaks) in 322 reported VP outbreaks in China during 2003–2008, followed by aquatic products (responsible for 16% of outbreaks) (Wu et al ., 2014). This is in contrast with data from other developed countries, where seafood products, mostly shellfish, are considered the food most associated with VP infection (McLaughlin et al , 2005; Su and Liu, 2007; Hara-Kudo and Kumagai, 2014). …”
Section: Introductioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Another national analysis has indicated that meat and meat products are the most common vehicle of VP infection (responsible for 18% of outbreaks) in 322 reported VP outbreaks in China during 2003–2008, followed by aquatic products (responsible for 16% of outbreaks) (Wu et al ., 2014). This is in contrast with data from other developed countries, where seafood products, mostly shellfish, are considered the food most associated with VP infection (McLaughlin et al , 2005; Su and Liu, 2007; Hara-Kudo and Kumagai, 2014). …”
Section: Introductioncontrasting
confidence: 94%
“…Previous studies have recognized eating raw or undercooked seafood (particularly shellfish) is a risk factor of VP infection in developed countries (Daniels et al ., 2000; Vuddhakul et al ., 2000; McLaughlin et al ., 2005; Su et al ., 2007; Hara-Kudo and Kumagai, 2014). In China, surveillance has indicated that seafood products had high concentrations of VP contamination (Yang et al ., 2008; Chen et al ., 2012; Zhang et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this review highlighted the need for developing relevant policies, legal requirements, and/or guidelines regarding the safety of oysters, particularly in developing countries, by considering contributing factors affecting the risk involved in consuming oysters and potential effects of climate change and ensuring their implementation through inspection and monitoring. The implementation of the shellfish harvesting policy adopted in the United States and guidelines governing the safety of seafood products in Japan are examples of efforts to reduce the risk of vibriosis (Alvarez, Solís, & Hwang, 2019; Hara‐Kudo & Kumagai, 2014). Additional efforts are required to encourage the harmonization of standards governing the safety of oysters between exporting and importing countries because oysters are traded in international markets.…”
Section: Overall Conclusionmentioning
confidence: 99%
“…3,4 Current epidemiological data show that VP has become a focus of food safety in Asia, South America and United States, while VP was first recognized as a cause of food-borne diseases in Osaka, Japan in 1951. [5][6][7] Although conventional culturing ensures the accuracy of determinations, and are optimum methods for VP identification, there still exist some shortcomings, such as long-time consumption and cumbersome practical application. Various approaches have been developed to obtain better performances of VP analysis, including enzyme-linked immunesorbent assay (ELISA), [8][9][10] DNA probe, 11 most probable number (MPN), 12,13 polymerase chain reaction (PCR), [14][15][16][17][18] loop-mediated isothermal amplification (LAMP), [19][20][21][22][23] and electrochemistry (EC).…”
Section: Introductionmentioning
confidence: 99%